Epidemiological Typing of Moraxella Catarrhalis by Pulsed Field Gel Electrophoresis. (1995) - Davison, Susan M; Low, Donald E; Cruz, Rene H; Beaulieu, Danielle; Scriver, Shelley R
Abstract : Pulsed field gel electrophoresis (pfge ) was used to compare 59 strains of Moraxella catarrhalis to evaluate pfge for the epidemiological typing of this organism. pfge -generated patterns were compared with those obtained by small fragment restriction enzyme analysis (rea ) and species-specific probe hybridization. The strains used in the study were isolated from various geographic locations and included proven epidemiologically related strains. pfge yielded more unique patterns than dna-dna hybridization – 30 versus 18, respectively – but fewer than rea, which generated 45 unique patterns. Strains that demonstrated the same rea pattern or dna-dna hybridization pattern did not always demonstrate the same pfge pattern. For example, in 23 epidemiologically unrelated strains that shared six rea patterns, pfge differentiated the isolates into 12 patterns. Conversely, strains that demonstrated the same pfge pattern did not always demonstrate the same rea pattern or hybridization pattern. For example, in 42 strains that shared 13 pfge patterns, rea differentiated the isolates into 31 patterns and dna-dna hybridization differentiated them into 16 patterns. However, compared with rea, pfge yielded less complex patterns that were more easily comparable, and compared with dna-dna hybridization, pfge was technically easier.